BC-Ni-ZIS photocatalyst for producing hydrogen peroxide and preparation method of BC-Ni-ZIS photocatalyst

By preparing nickel-supported biomass carbon and ZIS composite photocatalysts on corn coin carbon sources, the problem of unsatisfactory performance of monomer ZIS is solved, efficient hydrogen peroxide generation and charge separation are achieved, and photocatalytic performance is significantly improved.

CN119186610APending Publication Date: 2024-12-27HENAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411335070.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing monomer ZIS photocatalysts have poor performance in the production of hydrogen peroxide, poor surface acquisition of oxygen molecules and low charge separation efficiency, resulting in insufficient reaction selectivity and activity.

Method used

Using corn cobs as carbon source, nickel-supported biomass carbon material BC@Ni is prepared by high-temperature carbon thermal reduction, and ZIS is grown on its surface to form a BC@Ni@ZIS composite photocatalyst, and metal Ni promotes catalysis and porous structure are improved. Oxygen molecule diffusion and charge separation efficiency.

Benefits of technology

The hydrogen peroxide generation performance of the photocatalyst is significantly improved, reaching 3.25 times that of the monomer ZIS, and has good cycle stability and light capture ability, effectively avoiding the occurrence of competitive side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186610A_ABST
    Figure CN119186610A_ABST
Patent Text Reader

Abstract

The invention discloses a BC-Ni-ZIS photocatalyst for producing hydrogen peroxide and a preparation method of the BC-Ni-ZIS photocatalyst, BC-Ni with a porous structure is prepared by taking corncob as a biomass carbon source for carbon thermal reduction of nickel salt, and ZnIn2S4 (ZIS) is grown on the surface by taking BC-Ni as a matrix, so that the BC-Ni-ZIS photocatalyst is prepared. The biomass charcoal material (BC) is cheap and easy to obtain and has a rich pore structure and good hydrophobicity, a gas diffusion layer can be formed on the surface of the material in an aqueous solution, diffusion of oxygen molecules from a gas phase to surface active sites is facilitated, and the surface oxygen acquisition is improved. The BC enhances the light capturing ability of the photocatalyst while improving the surface oxygen acquisition of the photocatalyst. By regulating and controlling the compounding ratio of the BC-Ni-ZIS, the optimal photocatalytic hydrogen peroxide production performance of the BC-Ni-ZIS can reach 1101 [mu] mol g <-1 > h <-1 >, which is 3.25 times that of a monomer ZIS.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysts, and in particular to a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide and a preparation method thereof. Background Art

[0002] With the rapid development of the global economy, energy shortage and environmental degradation are becoming increasingly serious, and the development of new renewable clean energy has become crucial. Hydrogen peroxide, as a powerful and environmentally friendly oxidant, has the advantages of high energy density (60wt%, 3.0MJ / L), easy storage and transportation. Therefore, H2O2 has broad application prospects in the fields of energy and environment, and is widely used in disinfection, textile bleaching, chemical synthesis, wastewater treatment and small fuel cells. However, traditional production methods such as the anthraquinone method and the hydrogen-oxygen synthesis method have safety hazards in the production process, require the use of organic solvents, have many by-products, and consume a lot of energy, which does not conform to the concept of green and sustainable development. Photocatalytic synthesis of hydrogen peroxide is green, economical, and safe, with mild reaction conditions and simple operation, and has obvious advantages over traditional chemical synthesis methods.

[0003] Efficient photocatalytic production of hydrogen peroxide must ensure that enough oxygen molecules are transferred to the active sites to participate in the reaction. Due to the limited solubility and diffusion coefficient of oxygen molecules in the liquid phase, the surface oxygen availability of the photocatalyst is poor due to mass transfer, which seriously restricts the performance of photocatalytic hydrogen peroxide production. In addition, in addition to the two-electron oxygen reduction to generate hydrogen peroxide, there is also a competitive side reaction of four-electron oxygen reduction to generate H2O. The adsorption configuration of oxygen molecules on the surface of the photocatalyst fundamentally determines the reaction path and is a key factor affecting the reaction selectivity and activity.

[0004] As an important ternary metal sulfide, ZnIn2S4 (ZIS) has a large specific surface area and a high surface atomic exposure ratio, and has attracted much attention in the field of photocatalysis. However, monomer ZIS has poor photogenerated charge separation efficiency, low surface oxygen availability, and poor reaction selectivity, resulting in unsatisfactory photocatalytic performance in producing hydrogen peroxide. Summary of the invention

[0005] The purpose of the present invention is to solve the technical problem that the existing monomer ZIS has unsatisfactory performance when used for photocatalytic production of hydrogen peroxide, and to provide a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide and a preparation method thereof.

[0006] In order to solve the above-mentioned technical problems, the technical solution adopted by the present invention is:

[0007] A method for preparing a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide: using corn cobs as a biomass carbon source to carbon thermally reduce nickel salt to prepare BC@Ni with a porous structure, and then using BC@Ni as a matrix to grow ZIS on the surface to prepare the BC@Ni@ZIS photocatalyst.

[0008] As a further optimization of the preparation method of BC@Ni@ZIS photocatalyst for producing hydrogen peroxide of the present invention: the preparation method specifically comprises the following steps:

[0009] S1. Grind corn cobs, zinc salts and nickel salts to obtain a mixed powder, place the mixed powder in an inert atmosphere for calcination, and etch the calcined product with hydrochloric acid to obtain BC@Ni;

[0010] S2. Use the solvothermal method to grow ZIS on the surface of BC@Ni to prepare the BC@Ni@ZIS photocatalyst.

[0011] As a further optimization of the BC@Ni@ZIS photocatalyst preparation method for producing hydrogen peroxide of the present invention: the corn cob in step S1 is a corn cob that has been washed and dried, and the washing and drying process is specifically: the corn cob is repeatedly washed with deionized water and ethanol, and then dried in a vacuum drying oven at 60°C overnight.

[0012] As a further optimization of the BC@Ni@ZIS photocatalyst preparation method for producing hydrogen peroxide of the present invention: the zinc salt and the nickel salt in step S1 are Zn(CH3COO)2·2H2O and NiCl2·6H2O respectively.

[0013] As a further optimization of the BC@Ni@ZIS photocatalyst preparation method for producing hydrogen peroxide of the present invention: the calcination treatment in step S1 is specifically: heating from room temperature to 800°C at a heating rate of 5°C / min in an inert atmosphere and calcining for 2h, and then taking out after natural cooling in the tubular furnace.

[0014] As a further optimization of the method for preparing a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide according to the present invention: the inert atmosphere is nitrogen or argon.

[0015] As a further optimization of the method for preparing a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide according to the present invention: the concentration of the hydrochloric acid solution used for the hydrochloric acid etching in step S1 is 3M, and the etching time is 12 hours.

[0016] As a further optimization of the preparation method of a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide of the present invention: the step S2 is specifically: BC@Ni is placed in a glycerol solution with a volume fraction of 20% for ultrasonic dispersion, and then Zn(CH3COO)2·2H2O, InCl3·4H2O and C2H5NS are added and mixed evenly by magnetic stirring, and the obtained mixed solution is placed in a water bath at 80°C for reaction, and is naturally cooled to room temperature, and the BC@Ni@ZIS photocatalyst is obtained after washing and drying.

[0017] As a further optimization of the BC@Ni@ZIS photocatalyst preparation method for producing hydrogen peroxide of the present invention: the addition ratio of BC@Ni, Zn(CH3COO)2·2H2O, InCl3·4H2O and C2H5NS in step S2 is: 10 mg: 0.4 mmol: 0.8 mmol: 3.2 mmol.

[0018] The present invention also provides a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide. The photocatalyst is prepared by the above method and its photocatalytic hydrogen peroxide production performance can reach 1101 μmol g -1 h -1 .

[0019] The present invention has the following beneficial effects:

[0020] The present invention uses agricultural waste corn cobs as a carbon source, adds nickel salts and zinc salts, and prepares nickel-loaded biochar materials (BC@Ni) by a high-temperature carbon thermal reduction method, and uses this as a substrate to in-situ grow ZIS to prepare a BC@Ni@ZIS composite photocatalyst. BC is cheap and easy to obtain and has a rich pore structure and good hydrophobicity. The surface of the material can form a "gas diffusion layer" in an aqueous solution, which is conducive to the diffusion of oxygen molecules from the gas phase to the surface active sites, thereby improving its surface oxygen availability. Oxygen molecules tend to adopt an end-to-end adsorption configuration at the Ni metal site, which can significantly reduce the breakage of the OO bond and promote the OOH * The generation of intermediates effectively avoids the occurrence of competitive four-electron side reactions and improves the reaction selectivity. Metal Ni nanoparticles as co-catalysts realize the directional migration of photogenerated charges from ZIS to metal Ni, effectively improving the charge separation efficiency. In addition, BC enhances its light capture ability while improving the oxygen accessibility of the photocatalyst surface. By adjusting the composite ratio of BC@Ni and ZIS, the optimal photocatalytic hydrogen peroxide production performance of BC@Ni@ZIS reached 1101μmol g -1 h -1 , which is 3.25 times that of a single ZIS. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1XRD patterns of the photocatalysts prepared in Examples 1-6;

[0022] Figure 2 This is the SEM image of the photocatalyst prepared in Example 1;

[0023] Figure 3 This is the SEM image of the photocatalyst prepared in Example 2;

[0024] Figure 4 This is a SEM image of the photocatalyst prepared in Example 4;

[0025] Figure 5 This is the EDX image of the photocatalyst prepared in Example 4;

[0026] Figure 6 The hydrogen peroxide production performance of the photocatalysts prepared in Examples 1-6 and Comparative Examples 1-2;

[0027] Figure 7 The cyclic stability performance of the photocatalyst prepared in Example 4;

[0028] Figure 8 The UV-visible absorption spectra of the photocatalysts prepared in Examples 1, 2 and 4 are shown. DETAILED DESCRIPTION

[0029] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with embodiments, but the content of the present invention is not limited to the following embodiments. Example 1

[0030] Weigh 0.4mmol Zn(CH3COO)2·2H2O and 0.8mmol InCl3·4H2O, add to 40mL 20% glycerol solution, stir magnetically for 30min to mix evenly, add 3.2mmol C2H5NS, stir magnetically for 30min to mix evenly, place the obtained mixed solution in a water bath at 80℃ to react for 2h, cool naturally to room temperature, wash with deionized water and ethanol by centrifugation several times, and dry in a vacuum drying oven at 60℃ overnight to obtain ZIS. Figure 2 This is the SEM image of the photocatalyst ZIS prepared in Example 1 of the present invention. Figure 2 It can be seen that the ZIS is flake-shaped. Example 2

[0031] Weigh 5 g of washed and dried corn cobs, add 0.2 mmol NiCl2·6H2O and 1.6 mmol Zn(CH3COO)2·2H2O, and grind and mix for 30 min.

[0032] The obtained mixed sample was heated from room temperature to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcined for 2 hours, taken out while naturally cooling in the tube furnace, ground for 30 minutes, etched in a 3M hydrochloric acid solution for 12 hours, washed with deionized water until neutral, and dried in a vacuum drying oven at 60°C overnight to obtain BC@Ni. Figure 3 This is the SEM image of the photocatalyst BC@Ni prepared in Example 2 of the present invention. Figure 3 It can be seen that BC@Ni has a porous structure. Example 3

[0033] Weigh 5 g of washed and dried corn cobs, add 0.2 mmol NiCl2·6H2O and 1.6 mmol Zn(CH3COO)2·2H2O, and grind and mix for 30 min.

[0034] The obtained mixed sample was heated from room temperature to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcined for 2 hours, taken out while naturally cooling in the tube furnace, ground for 30 minutes, etched in a 3M hydrochloric acid solution for 12 hours, washed with deionized water until neutral, and dried in a vacuum drying oven at 60°C overnight to obtain BC@Ni.

[0035] 5 mg BC@Ni was ultrasonically dispersed in 40 mL of 20% glycerol solution, 0.4 mmol Zn(CH3COO)2·2H2O and 0.8 mmol InCl3·4H2O were added while stirring, and the mixture was mixed by magnetic stirring for 30 min. 3.2 mmol C2H5NS was added and mixed by magnetic stirring for 30 min. The mixed solution was placed in a water bath at 80°C to react for 2 h, cooled naturally to room temperature, washed several times by centrifugation with deionized water and ethanol, and dried in a vacuum drying oven at 60°C overnight to obtain BC@Ni-5@ZIS. Example 4

[0036] Weigh 5 g of washed and dried corn cobs, add 0.2 mmol NiCl2·6H2O and 1.6 mmol Zn(CH3COO)2·2H2O, and grind and mix for 30 min.

[0037] The obtained mixed sample was heated from room temperature to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcined for 2 hours, taken out while naturally cooling in the tube furnace, ground for 30 minutes, etched in a 3M hydrochloric acid solution for 12 hours, washed with deionized water until neutral, and dried in a vacuum drying oven at 60°C overnight to obtain BC@Ni.

[0038] 10 mg BC@Ni was weighed and ultrasonically dispersed in 40 mL of 20% glycerol solution, 0.4 mmol Zn(CH3COO)2·2H2O and 0.8 mmol InCl3·4H2O were added while stirring, and the mixture was mixed by magnetic stirring for 30 min. 3.2 mmol C2H5NS was added and mixed by magnetic stirring for 30 min. The mixed solution was placed in a water bath at 80°C to react for 2 h, cooled naturally to room temperature, washed several times by centrifugation with deionized water and ethanol, and dried in a vacuum drying oven at 60°C overnight to obtain BC@Ni-10@ZIS.

[0039] Figure 4 To prepare the SEM image of the photocatalyst BC@Ni-10@ZIS, Figure 4 It can be seen that the porous BC@Ni surface is loaded with flaky ZIS, and the two are well composited to form BC@Ni-10@ZIS. Figure 5 This is the EDX image of BC@Ni-10@ZIS. Figure 5 It can be clearly observed that Zn, In, S, Ni and C elements are uniformly distributed on BC@Ni-10@ZIS, proving the good composite of BC@Ni and ZIS.

[0040] The UV-visible absorption spectra of the photocatalysts prepared in Examples 1, 2 and 4 are as follows: Figure 8 As shown, BC@Ni has good light absorption performance in the visible light region, and its light absorption performance is significantly enhanced after ZIS and BC@Ni are composited. Example 5

[0041] Weigh 5 g of washed and dried corn cobs, add 0.2 mmol NiCl2·6H2O and 1.6 mmol Zn(CH3COO)2·2H2O, and grind and mix for 30 min.

[0042] The obtained mixed sample was heated from room temperature to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcined for 2 hours, taken out while naturally cooling in the tube furnace, ground for 30 minutes, etched in a 3M hydrochloric acid solution for 12 hours, washed with deionized water until neutral, and dried in a vacuum drying oven at 60°C overnight to obtain BC@Ni.

[0043] 15 mg BC@Ni was weighed and ultrasonically dispersed in 40 mL of 20% glycerol solution, 0.4 mmol Zn(CH3COO)2·2H2O and 0.8 mmol InCl3·4H2O were added while stirring, and the mixture was mixed by magnetic stirring for 30 min. 3.2 mmol C2H5NS was added and mixed by magnetic stirring for 30 min. The mixed solution was placed in a water bath at 80°C to react for 2 h, cooled naturally to room temperature, washed several times by centrifugation with deionized water and ethanol, and dried in a vacuum drying oven at 60°C overnight to obtain BC@Ni-15@ZIS. Example 6

[0044] Weigh 5 g of washed and dried corn cobs, add 0.2 mmol NiCl2·6H2O and 1.6 mmol Zn(CH3COO)2·2H2O, and grind and mix for 30 min.

[0045] The obtained mixed sample was heated from room temperature to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcined for 2 hours, taken out while naturally cooling in the tube furnace, ground for 30 minutes, etched in a 3M hydrochloric acid solution for 12 hours, washed with deionized water until neutral, and dried in a vacuum drying oven at 60°C overnight to obtain BC@Ni.

[0046] Weigh 20 mg BC@Ni and ultrasonically disperse it in 40 mL of 20% glycerol solution. Add 0.4 mmol Zn(CH3COO)2·2H2O and 0.8 mmol InCl3·4H2O while stirring, and mix evenly by magnetic stirring for 30 min. Add 3.2 mmol C2H5NS and mix evenly by magnetic stirring for 30 min. Place the obtained mixed solution in a water bath at 80°C to react for 2 h, cool naturally to room temperature, wash it with deionized water and ethanol by centrifugation several times, and dry it in a vacuum drying oven at 60°C overnight to obtain BC@Ni-20@ZIS. Comparative Example 1

[0047] Weigh 5 g of washed and dried corn cobs, add 0.2 mmol FeCl3·6H2O and 1.6 mmol Zn(CH3COO)2·2H2O, and grind and mix for 30 min.

[0048] The obtained mixed sample was heated from room temperature to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcined for 2 hours, taken out while naturally cooling in the tube furnace, ground for 30 minutes, etched in a 3M hydrochloric acid solution for 12 hours, washed with deionized water to neutrality, and dried in a vacuum drying oven at 60°C overnight to obtain BC@Fe.

[0049] 10 mg BC@Fe was weighed and ultrasonically dispersed in 40 mL of 20% glycerol solution. 0.4 mmol Zn(CH3COO)2·2H2O and 0.8 mmol InCl3·4H2O were added while stirring, and the mixture was mixed by magnetic stirring for 30 min. 3.2 mmol C2H5NS was added and mixed by magnetic stirring for 30 min. The mixed solution was placed in a water bath at 80°C to react for 2 h, cooled naturally to room temperature, washed several times by centrifugation with deionized water and ethanol, and dried in a vacuum drying oven at 60°C overnight to obtain BC@Fe-10@ZIS. Comparative Example 2

[0050] Weigh 5 g of melamine, add 0.2 mmol NiCl2·6H2O and 1.6 mmol Zn(CH3COO)2·2H2O, and grind and mix for 30 min.

[0051] The obtained mixed sample was heated from room temperature to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, calcined for 2 hours, taken out while naturally cooling in the tube furnace, ground for 30 minutes, etched in a 3M hydrochloric acid solution for 12 hours, washed with deionized water to neutrality, and dried in a vacuum drying oven at 60°C overnight to obtain C@Ni.

[0052] 10 mg C@Ni was ultrasonically dispersed in 40 mL of 20% glycerol solution, 0.4 mmol Zn(CH3COO)2·2H2O and 0.8 mmol InCl3·4H2O were added while stirring, and magnetic stirring was performed for 30 min to mix evenly. 3.2 mmol C2H5NS was added and magnetic stirring was performed for 30 min to mix evenly. The obtained mixed solution was placed in a water bath at 80°C to react for 2 h, and then naturally cooled to room temperature, washed by centrifugation with deionized water and ethanol for several times, and dried in a vacuum drying oven at 60°C overnight to obtain C@Ni-10@ZIS.

[0053] Figure 1 The XRD diagram of the photocatalyst prepared in Examples 1-6 of the present invention is shown in FIG. Figure 1 As shown in Figure 2, the XRD data of BC@Ni shows the characteristic peaks of elemental nickel, and the monomer ZIS shows good crystallinity. Due to the low loading and uniform dispersion of Ni, the XRD pattern of BC@Ni-x@ZIS does not show the characteristic peaks of Ni, but its EDX pattern ( Figure 5 ) proves the Ni loading. Figure 6 As shown, compared with ZIS, the photocatalytic performance of BC@Ni-x@ZIS (x=5, 10, 15, 20) is significantly enhanced, and with the change of BC@Ni content, its photocatalytic H2O2 production performance changes regularly, which verifies the good composite of BC@Ni and ZIS.

[0054] <Photocatalytic H2O2 production performance>

[0055] The photocatalytic H2O2 production experiment was carried out on the catalysts prepared in Examples 1 to 6 and Comparative Examples 1 to 2, and the specific steps are as follows:

[0056] (1) Weigh 20 mg of the catalyst and ultrasonically disperse it in 50 ml of a 10% isopropanol solution, stir it magnetically for 30 min in a dark environment, and perform a photocatalytic reaction using a xenon lamp as a light source (λ>420 nm);

[0057] (2) The reaction solution was calibrated using the iodine equivalent method to calculate the yield of H2O2;

[0058] (3) Carry out the cyclic test according to the methods described in (1) and (2), with each cycle lasting 1.5 hours.

[0059] Figure 6 The photocatalytic H2O2 production performance of the photocatalysts prepared in Examples 1 to 6 and Comparative Examples 1 to 2 is shown in Figure 1. The photocatalytic H2O2 production performance of ZIS monomer is poor, and BC@Ni has no photocatalytic H2O2 production activity. However, after the two are combined, BC@Ni-x@ZIS shows a significantly better photocatalytic H2O2 production performance than ZIS. Among them, BC@Ni-10@ZIS has the best performance of 1101 μmol g -1 h -1 The photocatalytic H2O2 production performances of BC@Fe-10@ZIS and C@Ni-10@ZIS were 303 μmol g -1 h -1 and 573 μmol g -1 h -1 , which is much lower than BC@Ni-10@ZIS, which proves the obvious advantages of metal Ni loading and corncob as carbon source in preparing BC@Ni@ZIS photocatalyst in producing hydrogen peroxide. Figure 7 As shown, BC@Ni-10@ZIS exhibited excellent photocatalytic H2O2 production performance within four cycles.

[0060] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide, characterized in that: BC@Ni with a porous structure was prepared by carbothermal reduction of nickel salt using corn cobs as biomass carbon source, and ZIS was then grown on the surface using BC@Ni as a matrix to prepare the BC@Ni@ZIS photocatalyst.

2. A method for preparing a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide as claimed in claim 1, characterized in that: The following steps are involved: S1. Grind corn cobs, zinc salts and nickel salts to obtain a mixed powder, place the mixed powder in an inert atmosphere for calcination, and etch the calcined product with hydrochloric acid to obtain BC@Ni; S2. Use the solvothermal method to grow ZIS on the surface of BC@Ni to prepare the BC@Ni@ZIS photocatalyst.

3. A method for preparing a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide as claimed in claim 1, characterized in that: The corn cob in step S1 is a corn cob that has been washed and dried, and the specific washing and drying process is: the corn cob is repeatedly washed with deionized water and ethanol, and then dried in a vacuum drying oven at 60° C. overnight.

4. A method for preparing a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide as claimed in claim 1, characterized in that: In the step S1, the zinc salt and the nickel salt are Zn(CH3COO)2·2H2O and NiCl2·6H2O respectively.

5. A method for preparing a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide as claimed in claim 1, characterized in that: The calcination treatment in step S1 is specifically as follows: heating from room temperature to 800° C. at a heating rate of 5° C. / min in an inert atmosphere and calcining for 2 hours, and then taking out after naturally cooling in the tube furnace.

6. A method for preparing a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide as claimed in claim 1 or 5, characterized in that: The inert atmosphere is nitrogen or argon.

7. A method for preparing a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide as claimed in claim 1, characterized in that: The concentration of the hydrochloric acid solution used for hydrochloric acid etching in step S1 is 3M, and the etching time is 12 hours.

8. A method for preparing a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide as claimed in claim 1, characterized in that: The step S2 specifically comprises: placing BC@Ni in a glycerol solution with a volume fraction of 20% for ultrasonic dispersion, then adding Zn(CH3COO)2·2H2O, InCl3·4H2O and C2H5NS and mixing them evenly by magnetic stirring, placing the obtained mixed solution in a water bath at 80°C for reaction, cooling naturally to room temperature, and obtaining the BC@Ni@ZIS photocatalyst after washing and drying.

9. A method for preparing a BC@Ni@ZIS photocatalyst for producing hydrogen peroxide as claimed in claim 8, characterized in that: In the step S2, the addition ratio of BC@Ni, Zn(CH3COO)2·2H2O, InCl3·4H2O and C2H5NS is: 10 mg: 0.4 mmol: 0.8 mmol: 3.2 mmol.

10. A BC@Ni@ZIS photocatalyst for producing hydrogen peroxide, characterized in that: The photocatalyst is prepared by the method described in any one of claims 1-9.